Knowledge and practice of periconceptional use of folic acid among primigravida mothers in Hospital Universiti Sains Malaysia - Roslan, Siti Nur Adila (Universiti Sains Malaysia, 2023)
Knowledge regarding folic acid intake plays important role in public health especially for women in the reproductive age, since lacking folate intake may cause several tube defects in baby during pregnancy. The aim of this study was to examine the knowledge and practice of periconceptional use of folic acid among primigravida mothers in Hospital USM. The questionnaire used in this study was primigravida mother’s knowledge and practice of periconceptional use of folic acid questionnaire adapted from study by Keshavarzi et.al. (2016). A total of 80 primigravida mothers in Hospital USM who fulfilled the inclusion and exclusion criteria were selected randomly. Data collected were statistically analysed using the SPSS software version 26.0. Pearson’s Correlation and Pearson’s Chi-Square were used for data analysis. As for the knowledge and practice level, the results show 1 (1.3%) for high knowledge and 63 (78.8%) for good practice respectively. There was as association between level of knowledge and level of practice (p = 0.221). Lastly, there is no association between age, educational level with the level of knowledge of periconceptional use of folic acid (p = 0.988) and (p = 0.743) respectively. In conclusion, the study finding demonstrated that primigravida mothers in Hospital USM have insufficient knowledge on the periconceptional use of folic acid and its management and could benefit from additional health education and campaign on that issue so that they are more knowledgeable and more competent in practice folic acid.